Fraudulent financial reporting trough financial ratios: case of banking sector in indonesia / Ossi Ferli - -, Ossi Ferli (UiTM Cawangan Johor, 2020)
Bank is a sector that has the most suspensions list in Indonesia from 2015-2017. This study aims to determine and analyze the financial ratios that influence the Fraudulent Financial Report for bank listed in IDX period 2015 - 2017. Financial ratios suspected to affect Fraudulent Financial Report are leverage, profitability, composition asset, liquidity and capital turnover. The final sample of this research are 40 banks. The technique analysis used in this research is logistic regression analysis. The hypothesis in this study was based on previous research and various other supporting theories. The results of this study showed that leverage and profitability had no significant effect on Banks Fraudulent Financial Report. Composition asset, liquidity and capital turnover has a significant effect on Banks Fraudulent Financial Report. There are no significant different financial ratios between bank with or without suspension, but there are different between fraudulent bank base on suspension data on OJK and fraudulent bank base on Beneish M Score.